Study of non-mesh technique of Desarda for inguinal hernia - Bansod, Atish Naresh; Jantli, Manjunatha; Umalkar, Rohan; Ansari, Amir; Tayade, Priyanka Charuhas; Awachar, Neha (International Surgery Journal, 2019)
Background: The tissue based techniques are still acceptable for primary inguinal hernia repair according to the European Hernia Society guidelines. Desarda’s no mesh technique, introduced in 2001, is a hernia repair method using an undetached strip of external oblique aponeurosis. This study compares the results with the studies done worldwide on Desarda’s technique. Methods: A total 120 cases were studied for 2 years (2015-2017), the primary outcomes measured were postoperative pain scores on day 1,7,30 using visual analogue scale, time taken to return to basic activities, time measured from skin incision to skin closer. Complications like cord oedema, seroma, fever, surgical site infection, chronic groin pain and recurrence were evaluated. Results: After a 15-month mean follow up period, 01 (0.83%) case had a recurrence among 120 patients. Mean operative time is 60 min; mean pain score on day-1, 7, 30 are 3.35, 0.9 and 0.008 respectively. Mean time taken to return back to work is 24 hours; complications like chronic groin pain, foreign bodysensation are not seen in single cases. These results are comparable with the studies done worldwide. Conclusions: In Desarda’s technique of inguinal hernia repair does not use mesh, so no complication related with the foreign body are seen and postoperative pain is less, early return to basic activities and Postoperative complications are less.